PERAN PEMBIMBING AKADEMIK (PA) PADA ERA ICT - HENDRIKUS MBIRA (JURNAL INFO KESEHATAN, 2013)
Role of Academic Advisors (PA) in the era of ICT (Information and Comunication Technology), in the present and future. Academic Advisors (PA) is an educator (teacher) established to guide the student in an educational institution, with the principal task of providing academic guidance and counseling. The meaning of relationship counseling is interactive, dynamic, and communicative, to assist students so that they can complete their studies on time. Discussion of Academic Advisors (PA), consisting of (1) Changes in technology in the Academic guidance, (2) Academic Guidance System based on ICT, (3) Advantages and Disadvantages of Academic Tutoring ICT, (4) Role of Academic Advisors and (5) Ethics Academic Guidance On-Line.